Evidence-based systematic review of cognitive rehabilitation, emotional, and family treatment studies for children with acquired brain injury literature: From 2006 to 2017. Issue 1 (2nd January 2020) - Laatsch, Linda; Dodd, Jonathan; Brown, Tanya; Ciccia, Angela; Connor, Felicia; Davis, Kim; Doherty, Meghan; Linden, Mark; Locascio, Gianna; Lundine, Jennifer; Murphy, Samantha; Nagele, Drew; et al.
ABSTRACT: This paper updates guidelines for effective treatments of children with specific types of acquired brain injury (ABI) published in 2007 with more recent evidence. A systematic search was conducted for articles published from 2006 to 2017. Full manuscripts describing treatments of children (post-birth to 18) with acquired brain injury were included if study was published in peer-reviewed journals and written in English. Two independent reviewers and a third, if conflicts existed, evaluated the methodological quality of studies with an Individual Study Review Form and a Joanna Briggs Institute (JBI) Critical Appraisal Checklist. Strength of study characteristics was used in development of practice guidelines. Fifty-six peer-reviewed articles, including 27 Class I studies, were included in the final analysis. Established guidelines for writing practice recommendations were used and 22 practice recommendations were written with details of potential treatment limitations. There was strong evidence for family/caregiver-focused interventions, as well as direct interventions to improve attention, memory, executive functioning, and emotional/behavioural functioning. A majority of the practice standards and guidelines provided evidence for the use of technology in delivery of interventions, representing an important trend in the field.